The use of pain killers (NSAIDs) in athletes: how large is the risk? - Fitzpatrick, D.; Leckie, T.; Heine, G.; Hodgson, L. (Journal of Science and Medicine in Sport, 2024)
Nonsteroidal anti inflammatory drug (NSAID) use is prevalent in sport however the risk associated with their use in athletes is not well understood. This review discusses the pharmacology of NSAIDs and the prevalence of their use in different sports and factors driving this. Use is very high in sports such as professional football and is sometimes used routinely without indication and without medical supervision. However there is a paucity of evidence in other sports. There is good evidence for use of NSAIDs following an acute injury but they may prevent normal tissue healing and remodelling if used longer term for MSK injuries. There are well known risks of cardiac, gastrointestinal and renal side effects but little specific data for athletes. Renal events are discussed in detail discussing the cumulative effect that NSAID use, dehydration and concurrent illness can have to produce significant renal and systemic insult. We then discuss a pragmatic prescribing model enabling clinicians to utilise the beneficial effects of these medications whilst minimising risks.